Child directed speech: Analysis of teacher-preschool children discourse / Nasimah Abdul Wahab - Nasimah, Abdul Wahab (2015)
A study on the characteristics of ‘child directed speech’ in the discourse between a preschool teacher and 12 preschool children in a Malaysian preschool was conducted to analyse the features associated in a classroom-oriented ‘child directed speech’. Pilot study was done pre-recording to anticipate difficulties that might be encountered in the course of conducting the study and in the process of video-recording the discourse happening between the teacher and the preschool children. Appropriate solutions were selected by the researcher to overcome those problems noted in the pilot study. Sampling was selected based on a given guidelines prepared by the researcher. The sampling was observed and recorded in the classroom setting. There was an interview conducted with the preschool teacher post-recording as to assess the obtained data. Questionnaire was given to the preschool teacher to collect the background information of the preschool children chosen for this study. Consent form was also distributed to the teacher to collect the teacher and the students’ approval in participating in this study. The findings indicate that six features of ‘child directed speech’ was found in the discourse between a Malaysian preschool teacher and 12 preschool children and they were: prosodic, lexical, complexity, redundancy, content and code-switching features.